Optimal complementary feeding practice and associated factors among children in Konso Zone, South Ethiopia - Abate, Meseret Girma; Wondimagegne, Zelalem Tafese; Belachew, Tefera (Frontiers in Nutrition, 2025)
IntroductionDespite the critical importance of complementary feeding, a significant number of young children in developing countries have suboptimal complementary feeding practices (OCFPs). After 6 months, a nutrient-dense, varied diet containing fruits and vegetables is crucial to complement breastfeeding. These appropriate complementary feeding practices have the potential to prevent all deaths among children. There were evidence gaps on OCFPs among children in the study area. Therefore, this study was conducted to fill this gap in order to design context-specific intervention.MethodA community-based cross-sectional study was conducted in Konso Zone, in South Ethiopia, among 337 randomly selected mothers having children 6–23 months of age. Data were collected using a pretested interviewer-administered questionnaire using the Kobo Toolbox and exported to SPSS Version 25 for cleaning and analysis. A multivariable binary logistic regression model was used to determine independent predictors of OCFP of mothers. Variables with a p-value < 0.05 at a 95% confidence interval (CI) were considered statistically significant in the final model.ResultsThe overall prevalence of OCFP was 14.8% (95% CI: 11.80%, 19.10%). The practices of timely initiation of complementary feeding, minimum meal frequency, and minimum dietary diversity (MDD) were 63.20%, 92.60%, and 20.50%, respectively. Mothers who were in advanced age (>35 years) (AOR = 3.32, 95% CL: 1.59, 6.95), exchanged food items from the market (AOR = 2.23, 95% CL: 1.03, 4.77), and had accessibility and availability of fruit and vegetables (AOR = 4.16, 95% CL: 1.83, 9.43) were independent predictors of OCFP.ConclusionThe findings indicate that a significantly low proportion of children met the minimum World Health Organization (WHO) complementary feeding recommendations. However, meal frequency showed relatively better adherence. Only one-fifth of young children achieved MDD, while more than two-thirds began complementary feeding earlier than the recommended 6-month threshold. To improve complementary feeding practices, cost-effective interventions such as increasing access to fruits and vegetables and encouraging mothers to trade homegrown food items in local markets to diversify their children’s diets could be beneficial. Additionally, targeted efforts should focus on enhancing key complementary feeding indicators of meal frequency, timely introduction of complementary foods, and achieving MDD to improve children’s nutritional needs.